Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Aktivitas dan Hasil Belajar Matematika Siswa Kelas XI Inklusi SMK - Baiq Dewi Hartatik; Hapipi Hapipi; Nurul Hikmah; Syahrul Azmi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research aims to determinethe effect of this learning model guided inquiry by the activities and learning outcomes of students in class XI inclusion in mathematical. To achieve these objectivies, aquasi experimental research designis used with post-test only non-equivalent control group design. The population in this study were all class XI students of SMK Negeri Mataram for the 2019/2020 academic year. Number of students in this population are 294 scattered in the 11 class. Samples are selected with using purposive sampling technique and selected class XI DKV A as experimental class and XI T Graphic as the control class. The instrument used to obtain student activity data wasthe student activity observation sheet while the essay question were used to obtain data on student learning outcomes. Statistical analysis of the data was performed using the t test at an error level of 5%. The data obtained shows that the experimental class learning outcomes increased by 24,5 (46 to 70,5) while thecontrol class learning outcomes increased by 16 (47,2 to 63,2). Statistical analysis of student learning outcomes shows that (2,57 > 1,67). The results of the statistical analysis are supported by an increase in student activity at each meeting.